Correlation of placental thickness with gestational age in antenatal women - Verma, Priyanka; Gupta, Monika; Verma, Shraddha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Accurate estimation of gestational age and fetal wellbeing is mandatory to ensure safe pregnancy and healthy delivery. With recent development in USG, basic scan, Doppler imaging and interventional radiology helped greatly in accurate estimation of gestational age and delivering timely care. The objectives of this study was to determine the USG placental thickness at the level of insertion of cord in antenatal women from gestational age 11 to 40 weeks. To correlate placental thickness with gestational age. To calculate composite gestational age from USG parameters; CRL, BPD, HC, AC, FL. To compare the relationship of menstrual gestational age with placental thickness and composite gestational age separately Methods: It is a comparative study of 2 years duration. Total 322 patients were included. Gestational age was determined from LMP. Patient’s routine obstetric USG was done and composite gestational age was calculated from fetal parameters like BPD, HC, AC and FL (CRL in 11 to 14 weeks). At the same time placental thickness was determined at the level of insertion of umbilical cord. The plane of USG image was adjusted so that the thickness measured from cord insertion is perpendicular to the margin of uterine wall. Results: The following parameters were noted: correlation of period of gestation (weeks) with composite gestational age (weeks) correlation of period of gestation (weeks) with gestational age calculated by placental thickness (weeks). Conclusions: Placental thickness can give an estimation of gestational age. The linear correlation and statistical compatibility of placental thickness makes it an alternate parameter for gestational age. Knowledge of correct gestational age helps in delivering proper antenatal care, assessing fetal wellbeing, identifying pathology at the earliest and timely decision of termination and providing safe motherhood.